Career Guidance Programs and the Impact They Have in Eradicating Gender Imbalances in STEM Education For Market Competitiveness - Adaobi Jennifer Iloakasia (PT. Pusmedia Group Indonesia, 2024)
Gender disparities in STEM fields have long hindered equal opportunities for women, limiting their participation and contributions to the global workforce. The study employed a descriptive survey research design to examine the impact of career guidance programs on reducing gender imbalances in STEM education and enhancing market competitiveness in secondary schools in Anambra State, Nigeria. A sample of 95 respondents from both public and private schools was selected using a multi-stage sampling technique. Data were collected through a structured questionnaire distributed electronically. Validity was ensured by expert review, and reliability was confirmed with a Cronbach’s Alpha of 0.81. Descriptive and inferential statistics, including the Kruskal-Wallis, Median, and Jonckheere-Terpstra tests, were used to analyze the data. The study found that career guidance programs significantly improve STEM awareness, reduce gender imbalances, and enhance market competitiveness in secondary schools. Public and private schools showed notable differences in STEM awareness and gender equity, with gender-sensitive counseling playing a key role in promoting competitiveness through improved gender balance in STEM education. Additionally, the study highlights the role of mentorship and female role models in guiding career choices, contributing to gender equality and empowering women to pursue competitive STEM careers